Hubungan Faktor Stres, Aktifitas Fisik dan Berat Badan dengan Kejadian Gangguan Siklus Menstruasi pada Remaja Putri Kelas XI di SMA Negeri 1 Sumber Rejo Tanggamus - dewi yuliana; hernida hernida (Jurnal Ilmu Keperawatan Indonesia, 2020)
The menstrual cycle is Time since the first day of menstrual until came the next period menstrual. While menstrual cyclel disorders where The process of menstrual began to get a bit irregular that which is in accordance with the schedule menstruation that is supposed to be occurs during the course of 2 -7 days with long menstrual cycle normally 22-23 days. Prevalence rate occurrence menstrual to teenager research data in the past year 13,7% have problem of  cycle menstrual that irregular. There are several factors could affect menstrual cycle disorders between in being stress, body activity, and height. Purpose of this research to knowing factor relations of stress, phisycal activity, and height with incident of menstrual cycle disorders at girl teenager class XI at SMAN 1 Sumberjo Tanggamus 2018. This research use method quantitative with design analityc and with approach cross sectional, done at May 2018 in 57 respondent consisting students class XI IPA,IPS, Bahasa at at SMAN 1 Sumberjo Tanggamus 2018, with using primer data, where data collection using  questionnaire sheet. Analysis used for looking relations of dependent and independent variable used test chi square (X²). The results of the study obtained significant relations between stress with menstrual cycle disorders incident (p-value=0,031). The existence of a significant relation exists between physical activity stress with menstrual cycle disorders incident (p-value=0,024), and there was no significant relations between height with menstrual cycle disorders incident (p-value=0,498). Advice for schools to give health counseling through school health units about ways to improve reproductive health in adolescents especially concerning menstrual cycle disorders in prevention.